Folate Status and Serum Folate Forms in a Population Without Fortification. (29th May 2020) - Potischman, Nancy; Yang, Lichen; Hao, Ling; Linet, Martha
Abstract: Objectives: To evaluate the presence and amounts of folate forms by strata of total folate in a population without fortification or supplementation. Methods: The Chinese Families and Children Cohort feasibility study evaluated the potential for follow-up of mothers and offspring who participated in the Community Intervention Program, a folate intervention program conducted in China during 1993–1996. The feasibility study was carried out during 2012. Subjects completed an 8-day protocol that included multiple questionnaires (on diet, physical activity, ultraviolet radiation exposure and other factors) and provided fasting blood samples that were processed in local hospitals. The samples were then shipped frozen to the US. CDC's Nutritional Biomarkers Branch laboratory, which analyzed the 183 serum samples by LC-MS/MS for 6 folate forms; total folate was the sum of 5 biologically active folate forms (excluding MeFox). Results: Median total folate concentration (nmol/L) in the 183 Chinese subjects (15.3 nmol/L) was comparable to US data prior to folic acid fortification (NHANES 1988–1994 = 18.4, NHANES 2005–2010 = 40.7). The mean total folate in the lowest quintile was 6.5 nmol/L suggesting folate insufficiency among those individuals with levels below 7 nmol/L. Forty-two of the 183 subjects had detectable levels of unmetabolized folic acid (UMFA) with the measurements of the remaining samples being below the detection limit (0.28 nmol/L). While most of the samples with detectable UMFA were in the top 2 quintiles of total folate (>18.6 nmol/L), all samples measured had fairly low UMFA concentrations (0.28–0.78 nmol/L). Of the 42 subjects with detectable UMFA, 36 lived in an urban center near Shanghai and may have had access to imported foods fortified with folic acid. None of the participants reported dietary supplement usage that contained folic acid. All folate forms also showed lower concentrations than the levels in the US post-fortification, with the distributions generally matching the lower half of the US distributions. Conclusions: These data suggest that low levels of UMFA are likely not a marker of excessive folic acid intakes and more likely a marker of limited dihydrofolate reductase enzyme activity. Funding Sources: Division of Cancer Control and Population Studies and the Division of Cancer Epidemiology and Genetics, National Cancer Institute, NIH.